2007
DOI: 10.1192/bjp.bp.106.034967
|View full text |Cite
|
Sign up to set email alerts
|

Screening young people for obsessive-compulsive disorder

Abstract: Obsessive-compulsive disorder (OCD) in young people is underrecognized and undertreated. Simple screening tools suitable for general practice and community services are needed. We created a seven-item self-report Short OCD Screener (SOCS) and administered itto young people aged 11-15 years, including 116 patients with OCD, 181 healthy community controls and 33 young people with other psychiatric diagnoses. The SOCS has excellent sensitivity of 0.97 (95% CI 0.91-0.98) to detect OCD cases. Its specificity is goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 14 publications
1
46
4
Order By: Relevance
“…In these settings OCS has usually been measured by means of various OCD screening questionnaires, the most commonly used being the 20-item survey form of the Leyton Obsessional Inventory-Children's Version (20-item LOI-CV) . Unlike other OCD screening tools, which in order to facilitate use consist of few items and are as a result unidimensional in nature (Hudziak et al 2006;Uher et al 2007), there is evidence to suggest that the factor structure of the 20-item LOI-CV is multidimensional (Bamber et al 2002;Berg et al 1988;Maggini et al 2001;Mathews et al 2007). Studies are inconsistent, however, in the number and nature of factors identified.…”
Section: Introductionmentioning
confidence: 88%
“…In these settings OCS has usually been measured by means of various OCD screening questionnaires, the most commonly used being the 20-item survey form of the Leyton Obsessional Inventory-Children's Version (20-item LOI-CV) . Unlike other OCD screening tools, which in order to facilitate use consist of few items and are as a result unidimensional in nature (Hudziak et al 2006;Uher et al 2007), there is evidence to suggest that the factor structure of the 20-item LOI-CV is multidimensional (Bamber et al 2002;Berg et al 1988;Maggini et al 2001;Mathews et al 2007). Studies are inconsistent, however, in the number and nature of factors identified.…”
Section: Introductionmentioning
confidence: 88%
“…17,29 The results showed that patients with higher SOCS scores had somewhat lesser improvement in HAI scores with CBT-HA over the 5-year period ( Figure 5) and that at 5 years the difference between CBT-HA and standard care was not significant (see Table 13). …”
Section: Influence Of Obsessional Symptoms On Outcomementioning
confidence: 96%
“…The first of these was that health anxietyfocused CBT (CBT-HA) would be less effective in patients who had additional comorbid pathology in the form of obsessional symptomatology [measured using the Short Obsessive-Compulsive disorder Screener (SOCS)]. 17 We also hypothesised that personality status would have an impact on the effectiveness of treatment, and that those with dependent personalities [measured using the Dependent Personality Questionnaire (DPQ)] 18 and other personality disorders 19 [measured using the Quick Personality Assessment Schedule (PAS-Q)], 20 which were subsequently converted into International Statistical Classification of Diseases, Eleventh Edition (ICD-11) 21 personality disorder categories, 22 would have a worse outcome with CBT-HA. We also expected that these comorbid disorders would be associated with increased costs.…”
Section: Research Objectivesmentioning
confidence: 99%
“…While self-report screening measures are available for the detection of OCD in children and adolescents (Bamber, Tamplin, Park, Kyte, & Goodyer, 2002;Berg, Rapoport, & Flament, 1986;Hudziak et al, 2006;Uher, Heyman, Mortimore, Frampton, & Goodman, 2007), these measures are not validated to discriminate between varying levels of OCD severity. Currently, the assessment of OCD severity in children and adolescents relies on structured clinical interviews and the most widely used measure is the interviewbased child version of the Yale-Brown ObsessiveCompulsive Scale (CY-BOCS, Goodman et al, 1989; Journal of Anxiety Disorders 22 (2008) 979-990 Scahill et al, 1997).…”
Section: Introductionmentioning
confidence: 98%